2020
DOI: 10.1002/ajum.12238
|View full text |Cite|
|
Sign up to set email alerts
|

Ruptured caseous calcification of the mitral annulus

Abstract: Mitral annular calcification (MAC) is considered a chronic and degenerative process involving the fibrous annulus of the mitral valve. The prevalence of MAC has been reported between 8% and 15%. It significantly increases with age, often seen in females, individuals with hypertension, chronic kidney disease and those with multiple cardiovascular risk factors. Caseous calcification of the mitral annulus (CCMA) (also known as caseoma) is a rare variant of MAC and should be considered in the differential diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The diameters of the masses in these cases were 36 × 19, 20 × 15, 6 × 5, and 40 × 30 mm, respectively. 5 , 6 , 7 , 8 Considering our 3 cases, the mean and minimum diameters of CCMA, resulting in suspected spontaneous fistula formation, were 23 and 6 mm at the major axis, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…The diameters of the masses in these cases were 36 × 19, 20 × 15, 6 × 5, and 40 × 30 mm, respectively. 5 , 6 , 7 , 8 Considering our 3 cases, the mean and minimum diameters of CCMA, resulting in suspected spontaneous fistula formation, were 23 and 6 mm at the major axis, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Sometimes a misdiagnosis as a tumour might lead to unnecessary exposure to explorative cardiotomy [ 3 ] . Caseous calcification is usually a benign condition of a dynamic process [ 8 , 9 , 10 ] . In a follow-up of 14 cases of caseous calcification in the prospective echocardiographic study by Deluca et al, it was found that three patients with mitral annulus calcification progressed to caseous calcification, and three patients with caseous calcification reverted to mitral annulus calcification during the study period [ 8 ] .…”
Section: Discussionmentioning
confidence: 99%
“…There was a reported case of caseous calcification with spontaneous resolution in a 60-year-old woman [ 9 ] . Another case report found a partial capsule rupture, including mobile remnants at the point of rupture with spontaneous resolution in asymptomatic patients [ 10 ] . Based on these reports and the absence of consensus in managing caseous calcification, we opted for only a follow-up of our patient.…”
Section: Discussionmentioning
confidence: 99%